Konseling Kelompok Teknik Self Management dan Teknik Realita Untuk Mereduksi Gaya Hidup Hedonis - Fauzi, Zainal; Hayati, Sri Ayatina (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
Hedonic lifestyle usually occurs in people who live in the city because they are pampered with all the facilities available, such as malls, restaurants, cafes, apartments, hotels and other facilities which are of course not far from home so they are very easy to reach for all groups, especially students SENIOR HIGH SCHOOL. In an effort to reduce hedonic lifestyles in students who pay attention to the context of time and applicability, especially in school settings, the counseling services that will be used are group counseling services, self-management techniques and reality techniques. This research aims to determine group counseling self-management techniques and reality techniques to reduce students' hedonic lifestyles. The type of research used is a quantitative research method, repeated measure experimental design. The reason researchers use this experimental pattern is to see the effects of a treatment on other variables. This research has a pretest and multiple posttest design and uses data analysis methods: descriptive analysis, normality test, sphericity test, and parametric statistics with one-way Anova test.